Analysis of visitor experience in Hungarian museum context using the PLS-SEM algorithm - Jászberényi, Melinda; Ginovszky-Bodnár, Dorottya (Muzeológia a Kultúrne Dedičstvo)
This article analyses the museum visitor experience through a quantitative questionnaire carried out at the Almásy Mansion Visitor’s Centre in Gyula, Hungary, using the PLS-SEM (partial least squares structural equation modeling) algorithm. The authors analysed the escapism dimension of Pine and Gilmore’s 4E model, suggesting refinement of the model in the context of museums. The aim of the research was to obtain a better understanding of the concepts of escapism, active involvement (as a key concept in the museum context), and how to set up a better measurement model of visitor experience. As a result this research, the authors were able to establish two valid models to examine the experience dimensions of the enhanced model and the components of the active involvement experience dimension.